Editorial [Hot Topic: Redox Status in the Pathophysiology of Inflammation and Therapeutic Targets (Executive Editor: Mena Soory)] - Soory, Mena (Infectious Disorders - Drug Targets, 2009)
I was able to compile this work due to an enthusiastic response from experts in the field. It encompasses the pathophysiology of inflammation relevant to physiological states, infections, autoimmune and metabolic diseases. This supplement demonstrates the increasing importance of redox-sensitive mechanisms during physiological function, inflammatory pathology, sepsis and carcinogenesis. The relevance of anti-oxidant defences and therapeutic applications, including current and future potential for nanotechnology is highlighted. It could play a strategic role in the adjunctive therapy of protracted chronic diseases by avoiding side effects of prescriptive medication. There are several advances in therapeutic utilisation of antioxidants produced by the host in response to pathophysiological states and those of dietary origin for their effective management. The diverse conditions addressed project the importance of oxidative stress during inflammation and effective methods of intervention which could benefit co-existing diseases with a similar progression. The ubiquitous nature of inflammation as a component of diverse acute and chronic pathological states underscores the importance of effective therapeutic targeting; often made difficult by complex interactions between receptors, therapeutic agents and host derived products. Streamlined application of these concepts for effective therapeutic targeting and focused delivery is a challenge for the future.